Analisis Motif dan Kepuasan Siswa Sekolah Dasar dalam Pemanfaatan YouTube sebagai Media Komunikasi Instruksional Bahasa Inggris - Gede Ryan Adi Putra; Ni Putu Yunita Anggreswari (MUKASI: Jurnal Ilmu Komunikasi, 2026)
The development of digital technology has changed learning practices, including the use of social media as a means of learning. YouTube is one of the popular platforms because it provides easily accessible audio-visual content. This study aims to analyze the use of YouTube as an English learning medium in SD Negeri 2 Sudaji as well as student responses based on the Uses and Gratifications Theory. This study uses a qualitative approach through observation, interviews, and document analysis with informants of English teachers and grade VI students. Data are analyzed through reduction, presentation, and conclusion drawn. The results of the study show that YouTube is effective in helping students understand English pronunciation and vocabulary. Student responses are positive, characterized by increased interest in learning, engagement, and confidence. From the perspective of Uses and Gratifications, YouTube caters to students' cognitive, emotional, social, and personal needs. However, there are obstacles such as focus distractions, technical problems, and the need for teacher guidance in content selection. Therefore, the use of YouTube as a learning medium in elementary schools will be effective if it is designed in a planned manner and accompanied by teachers.